Peran Kimia Medisinal Dalam Pengembangan Obat Antibakteri: Pendekatan Komputasi dan Eksplorasi Senyawa Bioaktif dari Sumber Alam - Saeful Amin; AlifiaFauziah; Najelina Shifa; Neneng Reva (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The development of bacterial resistance to conventional antibiotics is a serious challenge in the world of health, so innovative approaches are needed in the discovery of new antibacterial drugs. Medicinal chemistry plays a vital role in this process through interdisciplinary strategies that combine molecular design, computational technology, and natural resource exploration. Computational approaches such as molecular docking and deep learning allow efficient compound screening, accelerating the process of identifying potential drug candidates. On the other hand, natural resources provide a variety of bioactive compounds such as alkaloids, flavonoids, and terpenoids that have antibacterial activity. Case studies of the discovery of Halicin and mangiferin compounds emphasise the great potential of this method. Although challenges such as bioavailability and toxicity still exist, technological advances and the integration of computational approaches with ethnopharmaceuticals open up great opportunities in the development of new, more effective and selective antibacterial agents.